MEMBUMIKAN NILAI NILAI AKHLAQ DALAM KITAB AL-FIYAH IBNU MALIK DI PONDOK PESANTREN ROUDHLATUL MUTAALLIMIN AL AZIZIYAH II SEBANEH BANCARAN BANGKALAN - Afandi; Moh. Lutfi (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2021)
The word moral comes from Arabic which has become an uptake language. It is the plural form of Khuluqun which means